CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

James has to solve the given expression in the easiest way. The approach he should take is


A
Approach 1
No worries! We‘ve got your back. Try BYJU‘S free classes today!
B
Approach 2
No worries! We‘ve got your back. Try BYJU‘S free classes today!
C
Approach 3
Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
Open in App
Solution

The correct option is C Approach 3
Calculating the expression through each approach, we find:

Approach 1:

(23×413)×92

Multiply the first two terms:

23×413=2×43×13=839

Now,

839×92=8×939×2=7278=72÷678÷6=1213

Approach 2:

(413×92)×23

Multiply first two terms:

413×92=4×913×2=3626=36÷226÷2=1813

Now,

1813×23=18×213×3=3639=36÷339÷3=1213

Approach 3:

(23×92)×413

Multiply first two terms:

23×92=2×93×2=186=31

Now,

31×413=1213

The easiest approach to calculate the given expression is approach 3.

flag
Suggest Corrections
thumbs-up
0
Join BYJU'S Learning Program
similar_icon
Related Videos
thumbnail
lock
Addition and Subtraction of Decimals using Place Values
MATHEMATICS
Watch in App
Join BYJU'S Learning Program
CrossIcon